2018
DOI: 10.1111/are.13765
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary eucalyptol on stress markers, enzyme activities and immune indicators in serum and haematological characteristics of common carp (Cyprinus carpio ) exposed to toxic concentration of ambient copper

Abstract: In the present study, protective effects of dietary eucalyptol were investigated against copper toxicity in common carp (Cyprinus carpio). The fish were fed with diets supplemented with 0 (control), 0.5% and 1% eucalyptol for 14 days before exposure to 0.25 mg/L ambient copper for 7 days. Blood samples were taken from the fish before and 1, 3 and 7 days after copper challenge. Before copper challenge, eucalyptol significantly decrease serum aspartate aminotransferase (AST) activity, but increase blood WBC, RBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 57 publications
(115 reference statements)
4
21
0
Order By: Relevance
“…Moreover, 0.5% cineole significantly prevented the ammonia‐induced lysozyme elevation. The results are similar to those reported by (Hoseini, Hoseinifar, et al, ), which found dietary eucalyptol significantly mitigated copper‐induced changes in immune components in common carp. Gupta et al () also found that dietary microbial levan significantly mitigated fipronil‐induced immunosuppression.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Moreover, 0.5% cineole significantly prevented the ammonia‐induced lysozyme elevation. The results are similar to those reported by (Hoseini, Hoseinifar, et al, ), which found dietary eucalyptol significantly mitigated copper‐induced changes in immune components in common carp. Gupta et al () also found that dietary microbial levan significantly mitigated fipronil‐induced immunosuppression.…”
Section: Discussionsupporting
confidence: 91%
“…All the cineole levels were effective to reduce enzymes’ elevation after the ammonia challenge, but the most effective level was 0.5%, the only level significantly decreased serum LDH and ALT activities. Similar to the present results, dietary supplementation with eucalyptol significantly mitigated copper‐induced elevation in aminotransferase activity in common carp (Hoseini, Hoseinifar, & Doan, ). Abdel‐Tawwab () found that dietary herbal ( Panax quinquefolium ) supplementation significantly suppressed elevation in blood aminotransferase activity following copper exposure in Oreochromis niloticus .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Herbal materials are important in promoting fish immune and antioxidant capacity (Chakraborty, Horn, & Hancz, ; Hoseini, Hoseinifar, & Doan, ; Hoseini, Mirghaed, Iri, & Ghelichpour, ; Taheri Mirghaed, Hoseini, & Ghelichpour, ). A variety of herbal materials has been found to augment fish immune and antioxidant capacity, for example, Psidium guajava (Gobi et al, ), Toona sinensis (Wu, Liu, Chang, & Hsieh, ), Cynodon dactylon (Kaleeswaran, Ilavenil, & Ravikumar, ), Eriobotrya japonica (Hoseinifar, Khodadadian Zou, Doan, Kolangi Miandare, & Hoseini, ) and Salvia officinalis (Sönmez et al, ).…”
Section: Introductionmentioning
confidence: 99%